Docosane-Organosilica Microcapsules for Structural Composites with Thermal Energy Storage/Release Capability - Fredi, Giulia (Materials (Basel), 2019)
Organic phase change materials (PCMs) represent an effective solution to manage intermittent energy sources as the solar thermal energy. This work aims at encapsulating docosane in organosilica shells and at dispersing the produced capsules in epoxy/carbon laminates to manufacture multifunctional structural composites for thermal energy storage (TES). Microcapsules of different sizes were prepared by hydrolysis-condensation of methyltriethoxysilane (MTES) in an oil-in-water emulsion. X-ray diffraction (XRD) highlighted the difference in the crystalline structure of pristine and microencapsulated docosane, and (13)C solid-state nuclear magnetic resonance (NMR) evidenced the influence of microcapsules size on the shifts of the representative docosane signals, as a consequence of confinement effects, i.e., reduced chain mobility and interaction with the inner shell walls. A phase change enthalpy up to 143 J/g was determined via differential scanning calorimetry (DSC) on microcapsules, and tests at low scanning speed emphasized the differences in the crystallization behavior and allowed the calculation of the phase change activation energy of docosane, which increased upon encapsulation. Then, the possibility of embedding the microcapsules in an epoxy resin and in an epoxy/carbon laminate to produce a structural TES composite was investigated. The presence of microcapsules agglomerates and the poor capsule-epoxy adhesion, both evidenced by scanning electron microscopy (SEM), led to a decrease in the mechanical properties, as confirmed by three-point bending tests. Dynamic mechanical analysis (DMA) highlighted that the storage modulus decreased by 15% after docosane melting and that the glass transition temperature of the epoxy resin was not influenced by the PCM. The heat storage/release properties of the obtained laminates were proved through DSC and thermal camera imaging tests.